Key Factors Governing Microbial Community in Extremely Acidic Mine Drainage (pH <3) - Huang, Ye; Li, Xiu-Tong; Jiang, Zhen; Liang, Zong-Lin; Wang, Pei; Liu, Zheng-Hua; Li, Liang-Zhi; Yin, Hua-Qun; Jia, Yan; Huang, Zhong-Sheng; Liu, Shuang-Jiang; Jiang, Cheng-Ying (Frontiers in Microbiology, 2021)
The microbial community of acid mine drainage (AMD) fascinates researchers by their adaption and roles in shaping the environment. Molecular surveys have recently helped to enhance the understanding of the distribution, adaption strategy, and ecological function of microbial communities in extreme AMD environments. However, the interactions between the environment and microbial community of extremely acidic AMD (pH <3) from different mining areas kept unanswered questions. Here we measured physicochemical parameters and profiled the microbial community of AMD collected from four mining areas with different mineral types to provide a better understanding of biogeochemical processes within the extremely acidic water environment. The prominent physicochemical differences across the four mining areas were in SO42-, metal ions, and temperature, and distinct microbial diversity and community assemblages were also discovered in these areas. Mg2+ and SO42- were the predominant factors determining the microbial structure and prevalence of dominant taxa in AMD. Leptospirillum, Ferroplasma, and Acidithiobacillus were abundant but showed different occurrence patterns in AMD from different mining areas. More diverse communities and functional redundancy were identified in AMD of polymetallic mining areas compared with AMD of copper mining areas. Functional prediction revealed iron, sulfur, nitrogen, and carbon metabolisms driven by microorganisms were significantly correlated with Mg2+ and SO42-, Ca2+, temperature, and Fe2+, which distinguish microbial communities of copper mine AMD from that of polymetallic mine AMD. In summary, microbial diversity, composition, and metabolic potential were mainly shaped by Mg2+ and SO42- concentrations of AMD, suggesting that the substrate concentrations may contribute to the distinct microbiological profiles of AMD from different mining areas. These findings highlight the microbial community structure in extremely acidic AMD forming by types of minerals and the interactions of physicochemical parameters and microbiology, providing more clues of the microbial ecological function and adaptation mechanisms in the extremely acidic environment.